Estrangement in Ernest Hemingway‟s The Sun Also Rises - Ramya, A. (International Journal of Psychosocial Rehabilitation, 2020)
Ernest Hemingway occupies a towering place among the twentieth century post-war writers. The alienation in this century was the direct result of World War I that caused an all-pervasive destruction material, spiritual and moral. The Sun Also Rises exposes powerfully the theme of Estrangement in a very faithful manner. It is an authentic account of the sense of aimlessness; nihilism, despair and, above all, the sense of alienation. The Estrangement is conveyed to us through the recurrent imagery of feast that always ends with empty glasses and mopping-off of tables. The reality of this world is that faith in religion and God is usually disappointing; the prevailing ethics and social conventions are a sham and virtue and morality are mere cloaks for unashamed defiance of all basic principles of honesty, loyalty and righteousness. Hemingway knew that the entire might of the social machinery comes into action against the innocent joys and aspiration of an individual’s sentiments, which taken singly, every individual member of the social mass, holds dear to his heart.